MENGEMBANGKAN KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN DENGAN APE MEDIA AYAM BERTELUR - Ahmad Fachrurrazi; Anisa Uimadul Bilad (Melati Institute, 2023)
This study aims to determine the effect of laying hens media on the cognitive abilities of children aged 5-6 years at KB-RA Al-Kautsar Surabaya. Cognitive ability is a child's ability to think, observe, interpret, predict and do something to solve problems in acquiring knowledge. This research is focused on simple number operations: addition and subtraction. Chicken laying eggs media is one of the homemade APE (Educative Game Tools) which is very simple but useful in developing children's cognitive abilities. Through the medium of laying hens it is hoped that this will be the latest innovation in helping the development of children's cognitive abilities, especially regarding simple number operations: addition and subtraction. This study used the Pre-Experimental One Group Pretest-Postest Design with a sample of 20 children aged 5-6 years in group B at KB-RA Al-Kautsar Surabaya. The results of the data analysis show that the t-count value is 23.50, so the null hypothesis (H0) is rejected because the t-table value is smaller, namely 1.72913 for a significance level of 0.05 and 2.53948 for a significance level of 0.01 so it can be concluded that APE media laying hens influence on the cognitive abilities of children aged 5-6 years at KB-RA Al-Kautsar Surabaya. Especially cognitive abilities regarding simple number operations: addition and subtraction.